Armenia's and Georgia's contrasted positioning vis-à-vis the EU: between vocal centrality and strategic marginality. Issue 4 (2nd October 2019) - Delcour, Laure
ABSTRACT: In recent years, the conflict in Ukraine and the migrant crisis have shown that the events unfolding at Europe's fringes can affect the core. Therefore, enhanced knowledge about how countries on the edge position themselves vis-à-vis the centre is critical. This article seeks to contribute to a better understanding of the core-periphery relationship by investigating how neighbouring countries envision their role in the EU-driven socio-political order and exploring how their self-representations translate into political strategies toward the core. It offers a comparative analysis of Armenia's and Georgia's positioning vis-à-vis the EU since the launch of the European Neighbourhood Policy in 2004. The article highlights a sharp contrast between Georgia's vocal assertion of its centrality in Europe and Armenia's strategic choice of appearing marginal. However, as the article argues, this contrast needs to be nuanced: the positioning of a country as marginal or central does not consistently explain their degree of commitment vis-à-vis the EU.